Energy economics and access to electricity : three essays from Benin - (:unkn) unknown (My University, 2017)
Our research objectives are multiple. Front of all, we cover literature review in the fields of energy and economics. Specifically, we revisit regulation, pricing and well-being theories in sub-Saharan context where electricity sector is in crisis for a while. Subsequently, our results open up a deeper reflexion spectrum concerning sustainable development, mobile banking and innovation through access for all to clean energy. Finally, this thesis is articulated at the crossraods of theorical and applied research based on real study cases in Benin. Consequently, there is a strong need to expand applied research in African, and in Benin specifically because it constitutes a large scope of challenges and opportunities path beyond this work.
Keywords: African Research